(untitled) (Ágora de Heterodoxias, 2024)
Networking can be defined as the process of weaving, supported by links, an inter- or intra-organizational network with intersectoral scope. In the case of intragovernmental networks, these constitute a system of polycentric essence accentuated by the diversity of organizations, public, private, government, business, educational, financial, etc. that can constitute it, as well as by the various interests, capacities, resources that are inserted in the network, creating an intricate and complex system that leads to requiring regulatory systems focused on negotiation, transaction, alliance, cooperation. If we want to understand the variation in the behavior of individuals, in the case of the rulers of a country, such as a president, we need to look more closely at their personal and institutional circumstances. Describing and analyzing variation among presidents in the way they are setting up homophilic networks embedded in government structures is the goal of this article.